Perancangan UI/UX Pada Rebranding Website Line Wisata Karimunjawa Sebagai Media Informasi Pariwisata Kepulauan Karimunjawa - Bagus Saputro; T. Arie Setiawan Prasida; Birmanti Setia Utami (INTECOMS: Journal of Information Technology and Computer Science, 2024)
One of the most popular marine destinations for tourism is the Karimunjawa Islands. One unique draw of the Karimunjawa Islands is their pristine seas and breathtaking scenery. The local economy, particularly the tourism industry and Tour Operator, may benefit from this. The quality of the agency itself also affects a Tour Operator credibility, as does the ability of the portfolio it offers to potential clients to draw them in and utilize its services. The research will focus on UI/UX design for the rebranded Karimunjawa Tourism Line website, which uses the design thinking methodology to create a modern, user-friendly, and educational tourism information medium for the Karimunjawa Islands. Tests that were conducted using a Likert scale showed excellent results that the general public could use. To make the information on potential visitors' travel needs easy to grasp and accessible, the website has been built to present it in a concise, easily understood, and organized manner.Keywords: UI/UX, Website, Karimunjawa Tourism, Rebranding